Conjugation of Synthetic Trisaccharide of Staphylococcus aureus Type 8 Capsular Polysaccharide Elicits Antibodies Recognizing Intact Bacterium - Zhao, Ming; Qin, Chunjun; Li, Lingxin; Xie, Haotian; Ma, Beining; Zhou, Ziru; Yin, Jian; Hu, Jing (Frontiers in Chemistry, 2020)
Staphylococcus aureus causes wide range of life-threatening diseases. One of the powerful approaches for prevention and treatment is to develop efficient vaccine as antibiotic resistance greatly increases. S. aureus type 8 capsular polysaccharide (CP8) has showed great potential in vaccine development. An understanding of the immunogenicity of CP8 trisaccharide repeating unit is valuable for epitopefocused vaccine design and cost-efficient vaccine production. We report the chemical synthesis of conjugation-ready CP8 trisaccharide 1 bearing an amine linker, which effectively served for immunological evaluation. The trisaccharide 1-CRM197 conjugate elicited a robust IgG immune response in mice. Both sera antibodies and prepared monoclonal antibodies recognized S. aureus strain, demonstrating that synthetic trisaccharide 1 can be an efficient antigen for vaccine development.